2013
DOI: 10.1021/am4051266
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous RGB Emitting Au Nanoclusters in Chitosan Nanoparticles for Anticancer Gene Theranostics

Abstract: Advanced theranostic materials hold promise for targeted delivery of drugs, with the ability to follow the transport as well as its consequences. This should, ideally, be possible with minimum invasive surgery and having no or minimum cytotoxicity of the materials. It requires development of newer materials whose physical properties would allow for easy probe, which could carry the therapeutic molecules, which will be stable under physiological conditions, and at the same time would be able to permeate barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 65 publications
3
64
0
Order By: Relevance
“…Experimentally, luminescent Au nanoclusters in chitosan were synthesized by modifying a protocol established in our laboratory15 (Supplementary Fig. S1A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, luminescent Au nanoclusters in chitosan were synthesized by modifying a protocol established in our laboratory15 (Supplementary Fig. S1A,B).…”
Section: Resultsmentioning
confidence: 99%
“…The Au NCs were synthesized in the biopolymer chitosan using an established procedure . The average particle size was measured to be 0.83 ± 0.29 nm.…”
mentioning
confidence: 88%
“…The as‐synthesized NCs at pH 6.5 emitted at 612 nm, when excited by 300 nm light. When the pH of the medium was increased to 9.0 (using alkali) the emission peak shifted to 615 nm when recorded immediately; however, after 2 h the peak shifted to 627 nm with a significant decrease in intensity . On the other hand, when the pH was made acidic (3.5) then the emission peak appeared at 582 nm, accompanied by a sharp increase in intensity.…”
mentioning
confidence: 92%
“…The metal NPs immobilized on several matrices have attracted intensive research interest in large part because excellent interactions and bifunctional effects are expectable . For instance, it has been demonstrated that CS is one of the prime candidates to disperse and stabilize silver NPs to prepare potent antimicrobial CS–silver nanocomposites (NCs) . CS can make complexation with silver ions via free amino and hydroxyl groups in the CS chain, and hence can favor the stabilization of metal NPs …”
Section: Cs‐based Theranosticsmentioning
confidence: 99%